THE SECURITIZATION OF THE EGYPT GOVERNMENT IN 2019-2023 AS AN EFFORT TO RESOLVE THE GRAND ETHIOPIAN RENAISSANCE DAM ISSUE - Adiba Aliyya Rahma; Syahla Fitri Ayuni; Naufal Fauzan Deva Laksana; Septyanto Galan Prakoso (CMES (Center of Middle Eastern Studies), 2024)
The Grand Ethiopian Renaissance Dam (GERD) is a hydroelectric dam on the Blue Nile River in Ethiopia, constructed to address Ethiopia's electricity needs. However, the GERD has sparked conflicts with Lower Nile countries, particularly Egypt and Sudan. Egypt relies on the Nile River for over 90% of its water supply and views the dam as a significant threat to its water security. This perceived threat has prompted Egypt to adopt securitization measures to safeguard its national interests. This study employs a descriptive qualitative method, integrating securitization theory and national interest to analyze Egypt's securitization efforts concerning the GERD dispute from 2019 to 2023. The findings reveal that Egypt's securitization measures have not yielded significant outcomes. Furthermore, military action against the GERD is deemed impractical, as the dam's filling process has already been completed, and such action could cause severe flooding, endangering Egypt and its neighboring countries.